Prioritization of Managed Pork Supply Movements during a FMD Outbreak in the US - Patterson, Gilbert R.; Mohr, Alicia H.; Snider, Tim P.; Lindsay, Thomas A.; Davies, Peter R.; Goldsmith, Tim J.; Sampedro, Fernando (Frontiers in Veterinary Science, 2016)
In the event of a Foot and Mouth Disease (FMD) outbreak in the U.S., local, state, and federal authorities will implement a foreign animal disease emergency response plan restricting the pork supply chain movements and likely disrupting the continuity of the swine industry business. To minimize disruptions of the food supply while providing an effective response in an outbreak, it is necessary to have proactive measures in place to ensure minimal disease spread and maximum continuation of business. Therefore, it is critical to identify candidate movements for proactive risk assessments: those that are both most likely to contribute to disease spread and most necessary for business continuity. To do this, experts from production, harvest, retail, and allied pork industries assessed 30 common pork supply movements for risk of disease spread and industry criticality. The highest priority movements for conducting a risk assessment included the movement of weaned pigs originating from multiple sow farm sources to an offsite nursery or wean to finish facility, the movement of employees or commercial crews, the movement of vaccination crews, the movement of dedicated livestock hauling trucks, and the movement of commercial crews such as manure haulers and feed trucks onto, off, or between sites. These critical movements, along with several others identified in this study, will provide an initial guide for prioritization of risk management efforts and resources to be better prepared in the event of a FMD outbreak in the United States. By specifically and proactively targeting movements that experts agree are likely to spread the disease and are critical to the continuity of business operations, potentially catastrophic consequences in the event of an outbreak can be limited.